1985
DOI: 10.1016/0035-9203(85)90086-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathological aspects of trypanosomal meningoencephalitis in vervet monkeys after relapse following BerenilR treatment

Abstract: Four quarantined vervet monkeys were treated with intramuscular BerenilR in patent CNS infection after experimental trypanosome inoculation with Typanosoma brucei rhodesiense or T. brucei brucei. All four animals relapsed in the post-therapeutic survival time of 37 to 209 days when they had fully developed me~ngoencepha~tis in histological sections with the presence of interstitial intracerebral trypanosomes, which were confirmed in two monkeys by electron microscopy. In both, sequential samples of the serum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…2) (Hunter et al 1992 b). An increased neuroinflammatory reaction as a result of sub-curative drug treatment is not an idiosyncrasy of our model since this phenomenon has been reported by several researchers (Schmidt and Sayer, 1982 ;Poltera et al 1985) and could relate to the development of the PTRE found in human cases of HAT (Hunter et al 1992 a).…”
Section: Pathological Changesmentioning
confidence: 75%
“…2) (Hunter et al 1992 b). An increased neuroinflammatory reaction as a result of sub-curative drug treatment is not an idiosyncrasy of our model since this phenomenon has been reported by several researchers (Schmidt and Sayer, 1982 ;Poltera et al 1985) and could relate to the development of the PTRE found in human cases of HAT (Hunter et al 1992 a).…”
Section: Pathological Changesmentioning
confidence: 75%
“…The neuroinflammatory changes were most apparent in the white matter of the cerebral hemispheres but also occurred in the circumventricular areas. The neuroinflammatory picture has also been described in rodent [9] , [16] , [27] , [29] , [39] , [40] , [41] , [42] , [43] and primate [7] , [44] , [45] , [46] models of trypanosome infection. Although these studies reported a similar response to that described in human cases the development of a meningoencephalitis, with inflammatory cells infiltrating the brain parenchyma, was only seen on a few occasions and was more commonly associated with treatment failures [7] , [45] , [47] .…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate the spread of the parasite to its definite host, the cat, it has been suggested that persistent Toxoplasma infections in rodents may change the rodents’ behavior to show reduced avoidance of the predator cats 116 , 117 . It has also been suggested that African trypanosomes may hide in the brain, behind the BBB, between relapses in sub-optimally treated individuals 118 - 121 . In contrast to toxoplasmosis, there are no obvious changes in the behavior of the host caused be this parasite that could be associated with an increased rate of transmission.…”
Section: Consequences Of Parasite Invasion Of the Brainmentioning
confidence: 99%